Cuadros para los pontevedreses ‘Café Moderno’ y ‘Café el influjo de Valle-Inclán sobre Carlos Sobrino y Castelao - López Vázquez, José Manuel B. (Madrygal. Revista de Estudios Gallegos, 2009)
Valle-Inclán exerted a remarkable influence on the Galician artists that belonged to the 17 Generation. In the following article I analyze La Marquesa Rosalinda´s influence on Carlos Sobrino and Castelao, referring both the subject and some stylistic aspects connected with Symbolism and Art Nouveau.